2024
DOI: 10.1021/acs.iecr.3c04461
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Optical Biobased Polycarbonates with High Refractive Index and Low Birefringence

Zhengkai Li,
Heng Wang,
Hanwen Yan
et al.

Abstract: Biobased poly(isosorbide carbonate) (PIC) has the advantages of renewable sources, nontoxic environmental resistance, and high transparency. However, the optical properties of PIC are limited by the rigid alicyclic skeleton within polymer chains, resulting in a low refractive index and high birefringence. In this work, a novel diether anthraquinone (DAQ) monomer containing an aromatic cardo-ring and carbonyl-modified side group was designed and synthesized, which successfully improved the refractive index and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…It has been reported that the basic compounds like alkali metal salt and basic ionic liquids (ILs) can efficiently increase the conversion of monomers and reduce the reactivity difference between endo -OH and exo -OH. , Eo et al synthesized PICs with weight-average molar mass ( M w ) of 32,600 g/mol using cesium carbonate as the catalyst . Zhang et al screened different sodium salts and metal chlorides as catalysts, and concluded that metal chlorides were able to form hydrogen bonding with ISB and reduced the reactivity disparity of two hydroxyl groups .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the basic compounds like alkali metal salt and basic ionic liquids (ILs) can efficiently increase the conversion of monomers and reduce the reactivity difference between endo -OH and exo -OH. , Eo et al synthesized PICs with weight-average molar mass ( M w ) of 32,600 g/mol using cesium carbonate as the catalyst . Zhang et al screened different sodium salts and metal chlorides as catalysts, and concluded that metal chlorides were able to form hydrogen bonding with ISB and reduced the reactivity disparity of two hydroxyl groups .…”
Section: Introductionmentioning
confidence: 99%